Hamilton-Jacobi formulation for singular systems with second-order Lagrangians - Pimentel, B. M.; Teixeira, R. G. (Editrice Compositori Bologna, 1996)
Recently, the Hamilton-Jacobi formulation for first-order constrained systems has been developed. In such formalism the equations of motion are written as total differential equations in many variables. We generalize the Hamilton-Jacobi formulation for singular systems with second-order Lagrangians and apply this new formulation to Podolsky electrodynamics, comparing with the results obtained through Dirac's method.